The leapfrogging opportunity: The role of education in sustainable development and climate change mitigation. (24th October 2017) - Sarabhai, Kartikeya; Vyas, Purvi
Abstract: Recognising that the current paradigm of development which is fossil fuel based and high on consumption and waste is not a viable option for the future, developing countries need to take an alternative path towards sustainable development. All too often, they merely imitate solutions which are already being discarded in the West. The confidence levels in their own traditions and good practices are often low. With the knowledge which is available today, it is possible to leapfrog from low levels of development to sustainable development without going through conventional fossil fuel‐based economies. Education plays a key role in this transition. This article gives three examples—the Bus Rapid Transit System, the adoption of decentralised solar energy systems, and a large scale adoption of renewable energy—of how education plays a vital role in this process.